Impact of Sample Preservation and Manipulation on Insect Gut Microbiome Profiling. A Test Case With Fruit Flies (Diptera, Tephritidae) - De Cock, Maarten; Virgilio, Massimiliano; Vandamme, Peter; Augustinos, Antonios; Bourtzis, Kostas; Willems, Anne; De Meyer, Marc (Frontiers in Microbiology, 2019)
High Throughput sequencing (HTS) techniques are of great value for the investigation of microbial communities, and have been extensively used to study the gut microbiome. While most studies focus on the human gut, many others have investigated insects. However, because of the rapid spread of HTS techniques, a lot of variation exists in the protocols for sample preparation. In the present study, we investigated the impact of two widely adopted sample-processing procedures preceding library preparation i.e. preservation of insect tissue in 70% ethanol and sample dissection. We used the fruit fly Ceratitis capitata (Diptera: Tephritidae) as a model organism and set up two experiments, one comparing the effects of sample manipulation and preservation across life stages and the other across colony and wild populations. The results of this study show no major effects of dissection on the outcome of HTS. However, ethanol preservation did have effects on the recovered gut microbiome, the main effect being a significant reduction of the dominant genus, Providencia, in ethanol preserved samples. Less abundant bacterial groups were also affected resulting in altered microbial profiles obtained from samples preserved in 70% EtOH. These results have important implications for the planning of future studies and when comparing studies that used different sample preparation protocols.